SPECIFICITY OF HUMAN CAPITAL: EVOLUTION AND VALUE OF THE CONCEPT - Oksana V. Shulaeva (Статистика и экономика)
The paper examines the value of theconcept of general and speciﬁ c human capital proposed by G. S. Becker, from the 1960’s to the present time, the direction of its evolution and trends of further development. The evolution of the conceptof general and speciﬁc human capital isaimed at his heterogeneity reﬂ ection and directed towards the detailed approach,considering the job as a set of tasks andhuman capital as a set of required skillsfor these tasks and characterized by acertain type of speciﬁcity - industry, occupational and etc.